Prediksi Financial Distress Perusahaan Sektor Industri Consumer Cyclical - Imron HR; Ade Mulyati Maksudi; Imron Zabidi; Lim Hendra; Dwi Windu Suryono (Jurnal Manajemen, 2022)
This study attempts to investigate five company performance variables that affect the probability of financial distress in companies in the cyclical consumer sector. Companies have demand patterns that are strongly influenced by the business cycle, and face stiff competition in their own industries, both domestically and globally. On the other hand, the current massive technological developments have disrupted many companies in the cyclical consumer industry sector. Meanwhile, conditions that make it more difficult for companies around the world in general are the arrival of the COVID-19 pandemic that has hit the world since the end of 2019 until now has not ended. This study uses a binary logistic regression analysis technique with a sample of 10 cyclical consumer industrial sector companies during 2017-2021. The research findings show that there are three variables that have a significant negative effect on financial distress, namely: (1) cash flow from operating activity, (2) cash flow from financing activity, and (3) price – earnings ratio. Thus, if these companies can improve the performance of these three variables, they will be able to reduce financial distress. However, efforts to improve these three factors have encountered obstacles due to the arrival of the COVID-19 pandemic since the end of 2019 until now, which has not been completed, and even tends to exacerbate the company's financial difficulties.